2020
DOI: 10.3390/healthcare8040428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Food Art Therapy on the Self-Esteem, Self-Expression, and Social Skills of Persons with Mental Illness in Community Rehabilitation Facilities

Abstract: Persons with mental illness often have low self-esteem, a lack of self-expression, and poor social skills. This study used a quasi-experimental two-group pre-test-post-test design to investigate the effects of food art therapy on the self-esteem, self-expression, and social skills of persons with mental illness attending community rehabilitation facilities. The authors recruited persons with mental illness aged 18 years or older attending three community rehabilitation facilities. Participants in two rehabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Accordingly, selfpresentation on social media could significantly predict SMA in university students. Expression willingness is an interpersonal skill that selects appropriate actions and verbal expressions to communicate one's feelings (40). In this study, sharing photos or videos with others, and managing a personal homepage predicted expression willingness on social media, which is consist with previous study (27,28).…”
Section: Discussionsupporting
confidence: 76%
“…Accordingly, selfpresentation on social media could significantly predict SMA in university students. Expression willingness is an interpersonal skill that selects appropriate actions and verbal expressions to communicate one's feelings (40). In this study, sharing photos or videos with others, and managing a personal homepage predicted expression willingness on social media, which is consist with previous study (27,28).…”
Section: Discussionsupporting
confidence: 76%
“…Health education on diseases can also play a crucial role in improving individuals' understanding of their conditions, particularly in addressing misunderstandings and confusion (33,34), which can help improve negative symptoms and support disease rehabilitation (35,36). Additionally, social skills training has emerged as a promising rehabilitation technique, with evidence suggesting that it can improve social skills, increase social support, enhance selfesteem, and reduce self-stigma, ultimately leading to the improvement of negative symptoms (37)(38)(39). Recent studies have suggested that a combination of multiple intervention methods may be more effective (40)(41)(42), and thus, our study employed a combination of all three intervention methods.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, self-expression (immediately, 1-month follow-up) and self-efficacy (1-month followup) were significantly higher in the intervention group than in the control group. Because FAT activities are mainly related to expressing one's inner world and the main goal of these activities is to improve selfefficacy, 18 most studies have shown positive results for self-expression 23,[56][57][58] and self-efficacy, 20,57,59 regardless of age and health status. In this study, an analysis of participants' experiences also confirmed that they had enhanced their expression skills and gained a sense of confidence by endeavouring to complete challenging artworks continuously.…”
Section: Discussionmentioning
confidence: 99%
“…60 A study in which eight sessions of FAT over 1 month were conducted to rehabilitate persons with mental illness revealed an improvement in self-esteem immediately after the intervention. 58 Furthermore, Seifert et al 61 found that art-based therapy enables people with dementia to enhance their self-esteem. Another study that conducted creative art therapy involving diverse forms of artistic expression showed that it had positive effects on the self-esteem of elders with MCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation